Republic of Korea : Staff Report for the 2015 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Korea's growth momentum that had been building since early 2013 has stalled. Average quarterly growth rate declined to about 0.5 percent in the last three quarters of 2014 from about 1 percent in the previous four quarters. A turning point was the April 2014 Sewol ferry accident, which had a surprisingly large and persistent impact on consumer and investor sentiment. Growth is projected to be in a range centered about 3 percent in 2015. The main external risks include slower-than-expected growth in Korea's main trading partners, the impact of a persistently weak yen on Korean export industries, and side-effects from the global financial conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet